Do basic skills predict youth unemployment (16- to 24-year-olds) also when controlled for accomplished upper-secondary school? A cross-country comparison - Lundetræ, Kjersti [Verfasser]; Gabrielsen, Egil [Verfasser]; Mykletun, Reidar [Verfasser] (My University, 2010)
"Basic skills and educational level are closely related, and both might affect employment. Data from the Adult Literacy and Life Skills Survey were used to examine whether basic skills in terms of literacy and numeracy predicted youth unemployment (16-24 years) while controlling for educational level. Stepwise logistic regression showed that in Canada, Italy, Norway and the USA, low basic skills predicted youth employment. In Canada and the USA, basic skills at Level 1 increased the odds of being unemployed versus employed between two and four times compared to basic skills at Level 3 while controlling for educational level. As for Norway, when controlling for educational level, basic skills were nearly significant (p = 0.06), showing an odds ratio of 2.71." (Autorenreferat, BIBB-Doku)
Keywords: G 1.2.2.4 Arbeitslosigkeit; I 2.2.1 Westeuropa; I 2.3.2 Nordamerika; Beziehung Bildungssystem Beschäftigungssystem; Grundbildung; Bildungsniveau; Jugendarbeitslosigkeit; Internationaler Vergleich; Italien; Kanada; Norwegen; USA